Association of superoxide dismutase enzyme with staging and grade of differentiation colorectal cancer: A cross-sectional study. (October 2020) - Warsinggih,; Irawan, Budi; Labeda, Ibrahim; Lusikooy, Ronald Erasio; Sampetoding, Samuel; Kusuma, M. Ihwan; Uwuratuw, Julianus Aboyaman; Syarifuddin, Erwin; Prihantono,; Faruk, Muhammad
Abstract: Introduction: The increase of superoxide dismutase (SOD) level in colorectal cancer (CRC) patients based on the examination of staging and grade of differentiation still evidently represents a clinical problem. SOD level raises at a certain staging and reduce at a certain grade of differentiation. For that reason, this study aimed to assess the association between SOD and the variables analyzed in this study. Materials and methods: This study was observational study using a cross-sectional research design aimed to measure the association between SOD and staging as well as grade of differentiation in CRC incidence. The study was conducted in our institution from January until March 2018. Results: Statistical analyses of the data derived from the laboratory indicated that age and histopathological examination (TNM staging) had statistically significant correlation with SOD1 level. This significant correlation was proven from results of the statistical analyses of each variable at p = 0.039 (age) and p = 0.001 (TNM staging) respectively. Subsequent tests concerning the correlation between age and TNM staging on SOD1 level revealed that the study samples in the category of 30–49 age years old showed statistically significant correlation with SOD1 level with p = 0.009. Conclusion: The increase of grade of differentiation was proportional to the increase of SOD1 level as antioxidant against cancer in CRC patients. Highlights: The increase of SOD level is proportional to the increase of severity level of colorectal carcinogenesis. SOD1 level can be used as a valuable biomarker to detect cancer in the human colon. Age and TNM staging had significant association with SOD1 level among the colorectal cancer (CRC) patients.